Depressive symptoms are related to boredom proneness in patients receiving hospital care, regardless of alcohol status, lifestyle, or social support. (September 2021) - Constant, Aymery; Val-Laillet, David; Joubert, Anthony; Foret, Katia; Thibault, Ronan; Moirand, Romain
We examined the relationship between boredom proneness and psychological distress in patients receiving hospital care due either to excessive alcohol consumption or to gastrointestinal diseases. Sociodemographic data were collected together with boredom proneness subscales (internal/external lack of stimulation), psychological distress, physical activity, and social support. Boredom proneness due to a lack of external stimulation seemed to constitute a prominent personality trait in patients with alcohol consumption. But depressive symptoms were related only to boredom proneness due to a lack of internal stimulation in all patients, regardless of alcohol status, lifestyle, or social support. Potential implications for practice and future research are discussed.